Proactive Routing to Avoid Holes in Wireless Sensor Networks - Radhakrishnan, Kanthavel; R, Dhaya (Journal of ISMAC, 2024)
Wireless Sensor Networks (WSNs) are important for many uses, from environmental monitoring to smart cities, because they can collect and send data on their own. However, holes forming in the network, where nodes are either missing or not working, is a big problem that affects network performance and reliability. This study explores proactive routing strategies to prevent and reduce these holes in WSNs. The study examines the causes of holes, including physical damage, energy depletion, and poor node placement. The proposed study demonstrates the different proactive routing methods like energy-efficient protocols, geographic routing, and load balancing, which are essential for keeping the network working well. The study also look at hole detection methods and prediction tools that help find and stop holes early and finally, discusses the challenges and future work in the field, highlighting the need for solutions that can grow and use new technologies. This comprehensive review emphasizes how important proactive routing is for making WSNs work better and last longer.
Keywords: Wireless Sensor Networks (WSNs); Proactive Routing; Network Holes; Energy-Efficient Protocols; Geographic Routing; Load Balancing; Hole Detection; Predictive Models; Network Performance